Predicting effectiveness of marketing through analyzing emotional context in advertisement using deep learning - Arafat, Sheikh Mohammad; Islam, Rifatul; Rafi, Ishraque Arefin; Islam, Md. Rashedul (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.